Encouraging rural economic growth through farmer institutions and transparency for income optimization - Nurul Setianingrum; Nurhidayat, Nurhidayat (Indonesia Accounting Research Journal, 2024)
This research aims to evaluate the role of farmer institutions in optimizing profits and increasing socio-economic development in rural areas, with a focus on Sumber Candik Hamlet, Jember Regency as one of the coffee producers. This research is based on the importance of access to information, capital, infrastructure and markets to encourage agricultural innovation and sustainability of the coffee plantation sector. The methodology used is an ethnographic approach, where researchers spent seven months observing, interacting and interviewing coffee practitioners in Sumber Candik Hamlet. Research findings show that the information imbalance between farmers and traders, as described in asymmetric information theory by Akerlof (1970), causes farmers to often sell their crops at low prices. Meanwhile, producers in the Jember area sell processed coffee at much higher prices. These results underscore the importance of strengthening farmer institutions and increasing access to information to create more efficient and fair markets and optimize farmer profits. Apart from that, this research also emphasizes the need for policies that encourage more equal relations between economic actors and increase transparency in policy making to reduce the dominance of large capital owners. Strategic steps such as improving infrastructure and better access to information are expected to support more sustainable growth in the agricultural sector and improve the overall welfare of farmers.